Relação entre indicadores de qualidade de solo sob diferentes sistemas de manejo - Miranda, Alexandre Amadeu Cerqueira de (2018)
The changes in soil use associated to the management system have provided changes in soil ecosystem dynamics. Bioindicators are biological properties or processes within the soil that indicate the state of this ecosystem, and can be used in soil quality biomonitoring. Soil respiration occupies a key position in the carbon cycle of terrestrial ecosystems and is an excellent indicator of quality. Another important technique that can be used is Pfeiffer's circular chromatography. This reveals the vitality of the soil that manifests itself in its fullness through the primary and secondary metabolism of minerals by the enzymatic and dynamic activity of organic matter. Studies of this nature are important because they can provide a set of minimum data that can serve as reference for monitoring, evaluation and selection of soil quality indicators in different cropping and soil management systems. The objective of the research was to analyze the efflux of CO2 and the chemical, biological attributes of the soil in areas with different forms of use in the Municipality of Bananeiras, PB. For that, 5 environments with different use forms were selected. Basal respiration was performed monthly from July to December 2017. Changes in biological and quinic characteristics were evaluated using Pfeiffer's circular chromatography and chemical fertility analysis. The effects of the five soil use systems on their chemical and biological characteristics over time were evaluated using several statistical models: generalized least squares (GLS), logistic regression. The canonical correlation analysis (CCA) was used to study the relationship between the variables analyzed. The data collected during the period from July to December showed significant differences (p <0.001) both among the different forms of soil use and between the months in which the CO2 efflux was evaluated. When considering the day periods at the end of the evaluation months, it is also verified that the averages differ significantly, with daytime registering 271.86 mgCO2m-2h-1 and 318.38 mgCO2m-2h-1 for the night. The results of the joint analysis of Pfeiffer soil chromatography show that there are significant differences in all categories of qualitative scale evaluation between environments with different forms of soil use, pointing out that anthropic action has an impact on the dynamics of soil life , but there were also differences during the months in which the soils of these environments were analyzed. The canonical correlation model showed to be statistically significant with the first two correlation axes presenting values of 0.85 and 0.81, both with statistical significance. The percentage of explanatory power was low, remaining at 41% and 30%, respectively. The evaluation of the basal respiration and chromatographic of the soils of different environments showed that there are significant differences between these agroecosystems, pointing to possible negative impacts of anthropic action depending on the type of management performed after the native vegetation was removed. The chromatographic scale showed to be efficient to evaluate the main characteristics of the qualitative analysis of the chromatogram. Therefore, it is important to point out that the observation of sustainable management of agroecosystems is essential, bringing them closer to the dynamics of natural environments.